Smart Thinking How to Think Big, Innovate and Outperform Your Rivals - Art Markman (Platkus, 2012)
Think smart people are just born that way? Think again. Art Markman, one of the premier cognitive scientists in this field, demonstrates the difference between raw intelligence and \'smarter\' thinking. Using examples from his own lab and stories from the worlds of business and popular culture, Markman shows it is possible to learn to be a smarter thinker. In doing so, you can reap the benefits in every area of your life. Smart Thinking provides: 1. The means to replace self-limiting habits with new behaviours that foster smart thinking, 2. An understanding of the mind itself as well as memory, 3. The ability to define and solve problems more efficiently, 4. Ways to present and process information effectively. Using the tools and practical exercises provided in Smart Thinking, you too can access the skills needed to achieve your personal goals and create your own \'culture of smart thinking\' at work and home
Keywords: Thought and thinking. Critical thinking. Problem solving